Self-Concept as Predictors of Internet Addiction Among Undergraduate Students of Kwara State University, Nigeria - Hassan, Abdulhafis Adeyinka; Abdulkareem, Habibat Bolanle; Suleiman, Abdullahi (Bumi Publikasi Nusantara, 2024)
This study investigated self-concept as a predictor of internet addiction among Undergraduates at Kwara State University Malete. The objectives of the study were to examine the relationship between self-concept and internet addiction, gender, and the joint relationship among undergraduate students of Kwara State University, Malete. Four hundred University Undergraduates were selected through convenient sampling techniques which were used in sampling participants from their various departments within the school. Pearson Product Moment Correlation and Multiple Regression analysis were used to analyze the data collected. Results revealed that there is a significant relationship between self-concept and internet addiction (r = 0.097 p <0.05), there is no significant relationship between gender and internet addiction (r = 0.041 p <0.05), there is a joint relative relationship between self-concept, gender and internet addiction (F2, = 1.92, p <0.05) predict internet addiction (t = 0.639 p < 0.05) and self-concept statistically predict internet addiction (t =1.656 p<0.05). The study recommends among others that school counsellors and policymakers should organize seminars, workshops, and conferences to sensitize the students to the need to have realistic and objective self-assessment and Self-concept.